2012
DOI: 10.1074/jbc.m112.377028
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modulates Interleukin-1β-induced Phosphatidylinositol 3-Kinase and Nuclear Factor κB Signaling Pathways in Human Tenocytes

Abstract: Background: Resveratrol has been proposed to have beneficial health effects due to its anti-inflammatory properties. Results: Resveratrol suppressed IL-1␤-induced activation of NF-B and PI3K in a dose-and time-dependent manner. Conclusion: Anti-inflammatory effects of resveratrol may be mediated at least in part through inhibition/deacetylation of PI3K and NF-B. Significance: Activated Sirt-1 plays an essential role in anti-inflammatory effects of resveratrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 49 publications
2
68
1
Order By: Relevance
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 81%
“…SH5 is a cell permeable, reversible, substratecompetitive phosphatidylinositol analogue that inhibits AKT activation and the activation of select downstream substrates without decreasing phosphorylation of PDK-1 or other kinases downstream of RAS, such as MAPK. SH5 has been widely used as specific inhibitor of AKT in many cell lines (Lan et al 2011, Busch et al 2012, Qiao et al 2013, Yang et al 2013, acting as a potent inducer of apoptosis that selectively kills various types of cancer cells that contain high levels of active AKT. We used a second inhibitor, a AKT1/2 inhibitor, in additional experiments (Gilot et al 2010).…”
Section: Semen Collection and Processingmentioning
confidence: 99%
“…Furthermore, NF-κB was found to be an important component of the SDF-1/CXCR4 axis (32). NF-κB is a typical transcription factor that is activated through phosphorylation (23). A recent study showed that phosphorylation of NF-κB increases during hypoxia (33).…”
Section: Discussionmentioning
confidence: 99%
“…Res also prevents or mitigates the effects of eye diseases, such as retinal detachment and diabetic retinopathy (19)(20)(21)(22). The main target of Res is nuclear factor (NF)-κB, which is a major factor of the SDF-1/CXCR4 axis (23).…”
Section: Introductionmentioning
confidence: 99%